PIEZOELECTICITY AND ITS APPLICATIONS - PATEL, Mr. KUNJ BIHARI SINGH; KUMAR, Mr. RAVI; MISHRA, Mr. SACHIN DEV; Kr, Mr. RAKESH (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
The generation of electric field by applied pressure. It is observed in crystalline materials with no inversion symmetrical Piezoelectric ceramic materials are not piezoelectric until the random ferroelectric domains are aligned by a process known as POLING. When pressure is applied to an object, a negative charge is produced on the expanded side and a positive charge on the compressed side. Once the pressure is relieved, electrical current flows across the material. The output voltage obtained from a single piezoelectric crystal is in milli-volt (mV) range, which is different for different crystals. In order to achieve higher voltages, the piezoelectric crystals can be arranged in series. In this project the power is generated low voltage so this will be convert to higher voltage by using series voltage low (KVL)[3].